Tuberculosis Infection in the United States: Prevalence Estimates from the National Health and Nutrition Examination Survey, 2011-2012 - Miramontes, Roque (PLoS One, 2015)
BACKGROUND: Reexamining the prevalence of persons infected with tuberculosis (TB) is important to determine trends over time. In 2011–2012 a TB component was included in the National Health and Nutrition Examination Survey (NHANES) to estimate the reservoir of persons infected with TB. METHODS: Civilian, noninstitutionalized U.S. population survey participants aged 6 years and older were interviewed regarding their TB history and eligibility for the tuberculin skin test (TST) and interferon gamma release assay (IGRA) blood test. Once eligibility was confirmed, both tests were conducted. Prevalence and numbers of TST positive (10 mm or greater), IGRA positive, and both TST and IGRA positive were calculated by adjusting for the complex survey design after applying corrections for item nonresponse and digit preference in TST induration measurements. To examine TST positivity over time, data from NHANES 1999–2000 were reanalyzed using the same statistical methods. The TST was performed using Tubersol, a commercially available purified protein derivative (PPD), rather than PPD-S, which was the antigen used in NHANES 1999–2000. Prior patient history of TB vaccination was not collected in this study nor were patients examined for the presence of a Bacillus of Calmette and Guerin (BCG) vaccine scar. RESULTS: For NHANES 2011–2012, TST and IGRA results were available for 6,128 (78.4%) and 7,107 (90.9%) eligible participants, respectively. There was no significant difference between the percentage of the U.S. population that was TST positive in 2011–2012 (4.7% [95% CI 3.4–6.3]; 13,276,000 persons) compared with 1999–2000 (4.3%; 3.5–5.3). In 2011–2012 the percentage that was IGRA positive was 5.0% (4.2–5.8) and double TST and IGRA positivity was 2.1% (1.5–2.8). The point estimate of IGRA positivity prevalence in foreign-born persons (15.9%; 13.5–18.7) was lower than for TST (20.5%; 16.1–25.8) in 2011–2012. The point estimate of IGRA positivity prevalence in U.S.-born persons (2.8%; 2.0–3.8) was higher than for TST (1.5%; 0.9–2.6). CONCLUSIONS: No statistically significant decline in the overall estimated prevalence of TST positivity was detected from 1999–2000 to 2011–2012. The prevalence of TB infection, whether measured by TST or IGRA, remains lower among persons born in the United States compared with foreign-born persons.